PENGARUH STRUKTUR MODAL TERHADAP RASIO HASIL PENGEMBALIAN ATAS EKUITAS (ROE) PADA PERUSAHAAN PROPERTY DAN REAL ESTATE YANG TERDAFTAR DI BEI PERIODE TAHUN 2015 – 2017 - Yudi Pratama Putra; Ummul Khair; Yunita Lestari (Jurnal Akuntansi, Keuangan dan Teknologi Informasi Akuntansi, 2020)
Capital structure is needed in a company in order to achieve its long-term goals. Therefore, this must take the appropriate selection to optimalize the capital structure of company. This was as seen from Property and Real Estate companies as listed in BEI, which always decreased the financial statements of the period 2015–2017. It is suspected due to the less optimal of capital structure as a result the decrease performance of the companies. This research aims to determine the influence of capital structure on retrun on equity (roe) on Property and Real Estate company performance listed in BEI during 2015–2017. This research used quantitative method by using secondary data through documentation. The objects of this research are Property and Real Estate companies listed on the BEI. The sample was purposive sampling from 41 companies. The data analysis methods used multiple linear regression analyses. The results of this study showed that the debt and equity ratio to assets have no significant effect on the equity return ratio. The long-term debt to equity ratio has no effect on the return on equity ratio. The interest rate ratio found significant effect on the return on equity ratio. Simultaneously, the capital structure represented the debt ratio to asset, and equity, for long-term debt was equity ratio, while the interest rate ratio showed significantly to the return on equity ratio, as shown from equity result 23.0% and its residual rest 77% which influenced by other factors not included in this study. Keywords: capital structure, ROE